2018
DOI: 10.3389/fphys.2018.00618
|View full text |Cite
|
Sign up to set email alerts
|

Coactivation of TLR2 and TLR8 in Primary Human Monocytes Triggers a Distinct Inflammatory Signaling Response

Abstract: Innate immune signaling is essential to mount a fast and specific immune response to pathogens. Monocytes and macrophages are essential cells in the early response in their capacity as ubiquitous phagocytic cells. They phagocytose microorganisms or damaged cells and sense pathogen/damage-associated molecular patterns (PAMPs/DAMPs) through innate receptors such as Toll-like receptors (TLRs). We investigated a phenomenon where co-signaling from TLR2 and TLR8 in human primary monocytes provides a distinct immune … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 59 publications
(66 reference statements)
2
9
1
Order By: Relevance
“…B), confirming previous observations . Accordingly, we found that monocytes do accumulate IL‐12A mRNA upon TLR8 activation (data not shown), consistent with similar observations made by other groups . We also observed that CD14 + monocytes, unlike neutrophils (Fig.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…B), confirming previous observations . Accordingly, we found that monocytes do accumulate IL‐12A mRNA upon TLR8 activation (data not shown), consistent with similar observations made by other groups . We also observed that CD14 + monocytes, unlike neutrophils (Fig.…”
Section: Resultssupporting
confidence: 93%
“…However, while in neutrophils, R848 was a more potent trigger of IL‐23 production than LPS and in monocytes both agonists had near equal potency. Moreover, CD14 + monocytes could also produce IL‐12, but, consistent with the literature, only if incubated with TLR8 agonists. These differences in cellular responses to different agonists clearly demonstrate that the results obtained with our highly pure neutrophil populations are not due to their potential contamination with CD14 + monocytes.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This was largely dependent on TRIF and completely dependent on the capability to produce type I IFNs and on MyD88, proposedly through TLR2. It was also shown that co-stimulation of TLR2 and -8 inhibits IFNβ production by suppression of IRF5 [69]. This study proposed that activation of both TLRs shift T-cell differentiation from Th1 to Th17 through higher levels of IL-23 at the cost of IL-12p70 [69].…”
Section: Synergy Of Different Prrsmentioning
confidence: 84%
“…Several studies have focused on the genome-wide effects of TLR ligands on hematopoietic cells such as monocytes [54]. In the current study, we aimed to determine the specific roles of DUSPs and PKs in TLR4 signaling.…”
Section: Expression Landscape and Signaling Dynamics Of Dusps And Kinmentioning
confidence: 99%